Intervenção em socialização étnica: efeitos sobre a identidade e autoestima individual e grupal de crianças negras - Santos, Joana dos (2021)
Socialization is a process through which the child grasps the social world. It refers to the learning of rules, beliefs, and values that are shared by your social group and at the same time contributes to the understanding of social roles, as well as to the formation of an ethnic identity. Socialization depends on its socialization agents to achieve the objective of transmitting values, beliefs, expectations and cultural customs, of which parents and the school stand out. It is extremely important that the child finds expressive elements of his / her culture and origin in school, which will contribute to the formation of a positive self-concept and a positive self-esteem. However, this is not the reality of Brazilian schools. Studies provide clues that negative stereotypes, racism, and race discrimination still continue to mark children's school experiences. It is in this scenario that the present study aims to investigate the identity, individual and group self-esteem of black children, before and after an ethnic socialization program, observing if there are changes resulting from this intervention. To this end, the work is organized into three chapters. Chapter 1 is a review of the literature with the aim of offering theoretical support and fixing the study within the field of social psychology, while presenting the constructs that will be investigated. Chapter 2 consisted of a systematic review of the literature that aimed to capture the scenario of interventions to reduce racial prejudice in schools at national and international level, reaching the methodologies and theoretical contributions used for such interventions. The main result of the review was the fact that Brazilian social psychology did not dedicate itself to the elaboration of interventions in order to reduce racial prejudice. Chapter 3 consisted of an in-depth theoretical study with the objective of guiding the creation of ethnic socialization programs that can be successful both in reducing and improving the indices of identification with the group of belonging and with the group and individual self-esteem. In a multi-ethnic and racially unequal society, where there is underrepresentation of minority ethical groups in the spaces of power and understanding that this influences the way children will form their identities, it is essential that we redouble our efforts in order to promote education that citizenship, which contributes positively to the strengthened ethnic identities, greater self-esteem and consequently a better academic performance and psychological wellbeing.